2014
DOI: 10.1080/13548506.2014.959528
|View full text |Cite
|
Sign up to set email alerts
|

The role of emotion awareness and mood: Somatic complaints and social adjustment in late childhood

Abstract: Emotion awareness is a key concept related to different child adjustment outcomes. This relationship, influenced by mood, has been found in the preadolescent and adolescent population for somatic complaints. However, little is known in the case of younger children and when other adjustment outcomes are included. The objective of this work is to analyze the contribution of emotion awareness and mood upon different adjustment outcomes (somatic complaints, maladjustment, and peer sociometric status), in children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 33 publications
3
6
0
Order By: Relevance
“…These results show that mood plays an important role in the emergence of SHC. These findings are in line with previous studies (Verkuil et al, 2012, Villanueva et al, 2015 showing that less positive mood predicts higher SHC. Thus, selfreported and objective sleep duration and self-reported sleep quality can influence SHC either directly or indirectly via mood.…”
Section: Contrary To Our Results Van Laethem and Colleagues Found A supporting
confidence: 93%
See 1 more Smart Citation
“…These results show that mood plays an important role in the emergence of SHC. These findings are in line with previous studies (Verkuil et al, 2012, Villanueva et al, 2015 showing that less positive mood predicts higher SHC. Thus, selfreported and objective sleep duration and self-reported sleep quality can influence SHC either directly or indirectly via mood.…”
Section: Contrary To Our Results Van Laethem and Colleagues Found A supporting
confidence: 93%
“…Furthermore, in a correlational study, Villanueva, Górriz, Prado-Gascó and González (2015) found that higher negative mood was associated with more SHC.…”
Section: Introductionmentioning
confidence: 97%
“…Emotional driving is when a driver's emotional state deviates from the norm driving behavior (Dula and Geller, 2003). Some studies have pointed out that emotion has become one of the main causes of traffic accidents, among which the identification of emotion is the focus of driving emotion research (Villanueva et al, 2015).…”
Section: Eeg Based Studies In Emotional Drivingmentioning
confidence: 99%
“…In this sense, emotional consciousness is reinforced by moods. When there are few emotional competence skills, there is a tendency to generate a negative mood, which leads to high levels of prolonged stress [57]. In this sense, we propose that moods will mediate the relationship between EI and the emotional component of SWB (the balance between AP and NA).…”
Section: Introductionmentioning
confidence: 99%